Environmental preferences of adolescents within a low ecological footprint country - Bogner, Franz X.; Suarez, Bosque Rafael (Frontiers in Psychology, 2022)
As Cuba achieves one of the lowest per capita ecological footprints in the world, the country’s overshoot day was on 1 December 2019, while some European countries already reach this limit in February (e.g., Luxembourg), monitoring the environmental preferences of the Cuban younger generation may offer valuable behavioral or pedagogical insights into such a society. As accepted standardized measures exist in the scales of 2-Major Environmental Values (2-MEV) and the General Ecological Behavior (GEB), both measures are following the necessary psychometric requirement, as they have the unique advantage of repeated independent confirmation (and thus provide an external validity). These captured 40 items of reported behavior originating in six subscales that total in a single main cover score. The first one (2-MEV) monitors individual biocentric and anthropocentric preferences with a 20 item-set by relying upon these two higher-order factors of “Preservation” (PRE) and “Utilization” (UTL). Although many language versions already exist (33 in the case of the 2-MEV) for verifying validities and reliabilities of both scales, a country such as Cuba may affirm that this is due to expected cultural differences as well as their exceptionally low global footprint. Additionally, neither the individual connectedness with nature nor the diurnal preferences within the linear structural model showed a substantial relationship to PRE or UTL. Nevertheless, all the regression scores follow the expected positive or negative directions, albeit not all the fit scores turned out as satisfactorily. Apparently, the applied measures secure a good basis for measuring the attitudinal and behavioral framework, but will need further fine tuning to completely monitor the environmental preferences of Cuban adolescents.